1999
DOI: 10.1034/j.1399-3003.1999.13d26.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of myosin heavy chain in the vastus lateralis muscle in patients with COPD

Abstract: This study was designed to further characterize peripheral skeletal muscle alterations in patients with chronic obstructive pulmonary disease (COPD) and to evaluate the possible relationship between myosin heavy chain (MyoHC) isoform expression and exercise tolerance in these individuals.MyoHC composition from biopsy of the vastus lateralis muscle was examined in 12 COPD patients (forced expiratory volume in one second (FEV1)=319% predicted, peak oxygen consumption (V 'O 2 )=154 mL . kg -1 . min -1 ) and 10 ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 29 publications
3
72
1
Order By: Relevance
“…The first inevitable requirement is the muscle biopsy, since research at the cellular level is essential [9,[26][27][28]. The second requirement, however, is to pursue research goals as noninvasively as possible in these patients [29], which compelled the current authors to search for an acceptable alternative to the Bergströ m technique.…”
Section: Biological Comparisons Between Microbiopsy and The Bergströmmentioning
confidence: 99%
“…The first inevitable requirement is the muscle biopsy, since research at the cellular level is essential [9,[26][27][28]. The second requirement, however, is to pursue research goals as noninvasively as possible in these patients [29], which compelled the current authors to search for an acceptable alternative to the Bergströ m technique.…”
Section: Biological Comparisons Between Microbiopsy and The Bergströmmentioning
confidence: 99%
“…As already remarked, in fact, NSCLC patients usually presented symptoms similar to those related to COPD such as dyspnea, reduced exercise capacity, respiratory distress and a deteriorated quality of life. However, while in COPD have been well identified anatomical, physiological and biochemical alterations that are the basis of muscular dysfunction, as well as the biological mechanisms that may be the cause, namely the inactivity, the use of corticosteroids, systemic inflammation and oxidative stress [30,31], this has not yet occurred in cancer patients.…”
Section: Functional Assessmentmentioning
confidence: 99%
“…In contrast, other investigators [4,6,7] have reported that COPD patients have a lower proportion of type I fibres and an elevation in the per cent of type II fibres in the vastus lateralis muscle. In addition, two investigations [8,9] have demonstrated altered MyHC expression in vastus lateralis muscle biopsies from COPD patients. These investigations collectively indicate that alterations in muscle fibre composition induced by COPD may differ between humans and animals.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Such a shift would predispose skeletal muscle to greater fatigability and impair exercise tolerance. In addition, COPD patients with reduced work capacity present with alterations in peripheral skeletal muscle composition and structure, including altered fibre composition [4,6,7] and myosin heavy chain (MyHC) expression [8,9], atrophy of peripheral skeletal muscle type I and/or II fibres [7,10,11], and reductions in lean body mass [12]. Therefore, altered metabolic pathways, fibre transformation and fibre atrophy appear to underlie problems of enhanced skeletal muscle fatigability, reduced force production and exercise intolerance in patients with COPD.…”
mentioning
confidence: 99%